A Multi-USB Ports Solar-powered charging Station for Mobile Phones in Duracurve Sheds: From Educational Perspectives - Abraham Morales; Emmanuel John Lopez; Jay Manansala; Joeth Francisco Intal; Mark Christian Loria; Sherwin Mallari; Freneil Pampo (Universitas Pendidikan Indonesia (UPI), 2023)
The current study proposed a design for a Multi-USB Ports Solar-powered charging Station for Mobile Phones in Duracurve Sheds of Don Honorio Ventura State University. This research specifically aimed at addressing the issue of prohibiting the students of electrical engineering at Don Honorio Ventura State University (DHVSU) to charge their mobile phones inside the classrooms. This study, as quantitative research, utilized a developmental type of method, a Likert scale type of questionnaire through electronically generated forms (google form), and a thorough data analysis. The participants were composed of twenty (20) professionals and were chosen through the use of the purposive sampling technique. The study revealed that the proposed design for the solar-powered charging station, after considering its specifications, the materials and possible cost of its installation, its expected lifespan, and the total expenditure it will take could be an alternative way to provide a solution for each student’s concern, especially for educational purposes.